The first brazilian Residence of Family Medicine inside a private institution: the experience of residents - Danielle Harumi Miachiro Oyama; Erika da Cruz Campos (O Mundo da Saúde)
Family Medicine is a medical specialty that proposes a new model for medical professionals, with a differentiated approach to education centered in caring for individuals, in a continued and broader assistance coordinating also biopsychosocial components. Family doctors is accredited to take responsibility for the patient in hospital settings and to contribute to the co-ordination of cares, producing consequently a higher quality of service and a greater satisfaction of patients and relatives to received care. An approach centered in the person contributes, even in hospital settings, better conditions for both deciding on the use of diagnostic and therapeutic resources very often unnecessary or ineffective and also in care in the application of interventions strange to the patients’ home reality but which must be maintained after they returning to their homes, making extremely difficult their routine in a way that almost prevents adhesion top treatments. From these initial reflections, the program of medical residence in Family Medicine is approached by means of an individual analysis of daily activities and a debate about daily experiences from clinical cases assisted by female residents. After 6 months in residence we can certainly say that today we practice the kind of medicine we dream about and we know that in practice this kind of medicine makes a difference in the life of our patients and his relatives and which Family Medicine is possible We may also say in a country with so many social inequalities like ours, Family Medicine emerges as a viable alternative for a more just and human health care.